Концепт державної адміністративної служби України - Панова, Наталя (My University, 2021)
Дисертація є науковим дослідженням державної адміністративної служби, концептуальних засад її здійснення і правового регулювання, в якому охарактеризовано принципи, категорії посад державної служби, право на державну адміністративну службу, вимоги до кандидатів на посади державної служби, правовий статус державного адміністративного службовця, дисциплінарну відповідальність державного адміністративного службовця, і надано пропозиції щодо удосконалення чинного законодавства у цій сфері. Визначено поняття та охарактеризовано сутність державної адміністративної служби. Виокремлено загальні (публічність; професійність; політична неупередженість; спрямованість на практичне виконання завдань і функцій держави; фінансування за рахунок коштів державного бюджету) та спеціальні (регламентування законодавством у сфері державної служби, яке має відомчо-функціональний характер; місце проходження виключно в державних органах та в їх апараті або секретаріаті; проходження служби пов’язано з присвоєнням рангів; характерною є загальна дисциплінарна відповідальність) ознаки державної адміністративної служби. Визначено та охарактеризовано систему принципів, на яких ґрунтується державна адміністративна служба. Охарактеризовано сучасний стан правового регулювання державної адміністративної служби. Встановлено, що законодавство про державну адміністративну службу являє собою, на теперішній час, сукупність (а не систему) законів та підзаконних нормативно-правових актів (переважно відомчого характеру), що регулюють суспільні відносини щодо її організації та функціонування, і службові відносини щодо вступу на службу, її проходження та припинення. Виокремлено в залежності від змістовної спрямованості такі види нормативно-правових актів Кабінету Міністрів України та НАДС у сфері державної адміністративної служби: а) інституційні; б) кадрові; в) упорядковуючі; г) процедурні. Досліджено право на державну адміністративну службу як поліструктурне поняття. Виокремлено такі основні структурні елементи права на державну адміністративну службу у відповідності до його змістовно-розширювальної характеристики: 1) право на доступ до служби; 2) право на призначення на посаду; 3) право на проходження служби; 4) право на захист права на службу. Проаналізовано законодавство зарубіжних країн щодо регулювання державної адміністративної служби та визначено можливості запровадження ряду положень в умовах України. Запропоновано: зміни і доповнення до чинного законодавства України з питань державної служби; прийняття Кодексу державної адміністративної служби України.

The dissertation is a scientific research of the public administrative service, conceptual bases of its implementation and legal regulation, which describes the principles, categories of public service positions, the right to public service, requirements for candidates for public service positions, legal status of public servants, disciplinary liability of public servants, employee and provided suggestions for improving existing legislation in this area. It is defined the concept and characterized the essence of the public administrative service. There are general (publicity; professionalism; political impartiality; focus on the practical implementation of tasks and functions of the state; funding from the state budget) and special (regulation of legislation in the field of public service, which has a departmental and functional nature; place exclusively in government agencies and in their staff or secretariat, service is associated with the assignment of ranks, is characterized by general disciplinary responsibility) features of the public administrative service. It is defined and characterized the system of principles on which the public administrative service is based. The current state of legal regulation of the state administrative service is characterized. It is established that the legislation on the public administrative service is, at present, a set (rather than a system) of laws and bylaws (mostly departmental) governing public relations for its organization and functioning, and official relations for joining service, its passing and termination. Depending on the content, the following types of normative legal acts of the Cabinet of Ministers of Ukraine and the NAPS in the field of public administrative service are singled out: a) institutional; b) personnel; c) streamlining; d) procedural. It is studied the right to public administrative service as a polystructural concept. The main structural elements of the right to public administrative service in accordance with its content and expansion characteristics are identified: 1) the right to access the service; 2) the right to be appointed to the position; 3) the right to serve; 4) the right to protection of the right to service. The legal nature of disciplinary liability of public servants is determined and the legal grounds for bringing public servants to this type of liability are highlighted. The concept and content of disciplinary sanctions applied to public servants in case of disciplinary misconduct are defined and the main conditions of their application are highlighted. Disciplinary proceedings are described as an internal administrative procedure. It is clarified the content of the main guarantees of the rights of public servants during disciplinary proceedings and the application of disciplinary sanctions. It is analyzed the legislation of foreign countries on the regulation of the public administrative service and the possibilities of introducing a number of provisions in the conditions of Ukraine are determined. It is proposed: changes and additions to the current legislation of Ukraine on public service; adoption of the Code of the Public Administrative Service of Ukraine.
діс. д.ю.н. 12.00.07
Панова Н.С. Концепт державної адміністративної служби України : дис.. … д-ра.. юрид наук : 12.00.07 / Панова Наталя Сергіївна. – Одеса, 2021. – 427 с.
Keywords: державна адміністративна служба; державний адміністративний службовець; право на доступ до державної адміністративної служби; право на призначення на посаду державної адміністративної служби; право на проходження державної адміністративної служби; право на захист права на державну адміністративну службу; public administrative service; public administrative employee; the right to access the public administrative service; the right to be appointed to the position of the public administrative service; the right to the public administrative service; the right to protection of the right to the public administrative service